2018
DOI: 10.1111/ddi.12736
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the distribution and compositional variation of plant communities at the continental scale

Abstract: Aim We investigate whether (1) environmental predictors allow to delineate the distribution of discrete community types at the continental scale and (2) how data completeness influences model generalization in relation to the compositional variation of the modelled entities. Location Europe. Methods We used comprehensive datasets of two community types of conservation concern in Europe: acidophilous beech forests and base‐rich fens. We computed community distribution models (CDMs) calibrated with environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 68 publications
4
47
0
1
Order By: Relevance
“…This demonstrates a high potential of distribution modelling methods also for prediction of community‐level entities such as VTs, even at very high resolutions and for broad extents, given that appropriate predictor data are available (see Figure , for example). Our results are in accordance with other DM studies, operating with targets above species level, and on similar or larger spatial domains (Jiménez‐Alfaro et al., ; Mücher et al., ). Jiménez‐Alfaro et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This demonstrates a high potential of distribution modelling methods also for prediction of community‐level entities such as VTs, even at very high resolutions and for broad extents, given that appropriate predictor data are available (see Figure , for example). Our results are in accordance with other DM studies, operating with targets above species level, and on similar or larger spatial domains (Jiménez‐Alfaro et al., ; Mücher et al., ). Jiménez‐Alfaro et al.…”
Section: Discussionsupporting
confidence: 93%
“…Jiménez‐Alfaro et al. () also showed that DM of community‐level targets is a significant improvement to existing vegetation maps over the European continent, supplementing under‐sampled areas.…”
Section: Discussionmentioning
confidence: 98%
“…Changes in fen vegetation over the past few decades have raised conservation concerns in Europe and North America (Verhoeven et al., ; Jacobson et al., ; Fojt, ; van Diggelen et al., , ; Jímenez‐Alfaro et al., ) and have been variously ascribed to eutrophication, invasive species, or changes in hydrology or disturbance regime. The relative importance of hydrology and traditional management activities (mowing, grazing, burning, turf cutting) has been much debated, especially in Europe (Fojt and Harding, ; Opdekamp et al., ).…”
mentioning
confidence: 99%
“…Spatial habitat modelling (SHM) for settings FRVs of habitat types (continued) Suitability maps can be used to estimate range parameters (i.e. environmental driver) as well, such as the area of occupancy, useful for assessing the conservation status at both regional and continental (Jiménez-Alfaro et al, 2018; scales. • terrestrial mammals (Table A2.1);…”
Section: Spatial Modellingmentioning
confidence: 99%